2021
DOI: 10.1080/09540121.2021.1944601
|View full text |Cite
|
Sign up to set email alerts
|

ART initiation among women newly diagnosed with HIV in a contraceptive trial in sub-Saharan Africa

Abstract: Current guidelines recommend starting antiretroviral therapy (ART) as soon as possible after HIV diagnosis to reduce morbidity, mortality and onward HIV transmission. We examined factors influencing ART initiation by women who seroconverted during the Evidence for Contraceptive Options and HIV Outcomes (ECHO) Trial. ECHO, conducted between 2015 and 2018, enrolled HIV-negative, sexually active women, aged 16-35 years, from four African countries. Follow-up was 12-18 months, with quarterly HIV testing. Women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…On patient’s education levels, compared to tertiary education incomplete basic education, and secondary education explained a 9% and 6% positive association with rapid ART-initiation [aHR 1.09, 95%CI: (1.02-1.20) versus aHR=1.06, 95%CI: (1.01-1.12)] respectively. This association was however not reported from a recent study from Africa which observed no correlation [93]. Comparably, the likelihood of rapid ART-initiation was increased by 7% in Northern region and by 6% in Southern region compared to the Central region of Malawi ( p= 0.001).…”
Section: Resultscontrasting
confidence: 59%
See 3 more Smart Citations
“…On patient’s education levels, compared to tertiary education incomplete basic education, and secondary education explained a 9% and 6% positive association with rapid ART-initiation [aHR 1.09, 95%CI: (1.02-1.20) versus aHR=1.06, 95%CI: (1.01-1.12)] respectively. This association was however not reported from a recent study from Africa which observed no correlation [93]. Comparably, the likelihood of rapid ART-initiation was increased by 7% in Northern region and by 6% in Southern region compared to the Central region of Malawi ( p= 0.001).…”
Section: Resultscontrasting
confidence: 59%
“…On health facility types as a factor influencing ART-initiation, secondary and tertiary healthcare facilities were associated with 21% [aHR 0.79, 95%CI: (0.73-0.86) and 14% [aHR 0.86, 95%CI: (0.79-0.93), negative association with early ART-initiation compared to primary health facilities. The findings also demonstrated that contraceptive use likewise acted as a barrier to rapid ART-initiation and was associated with delayed initiation by 7% - a different finding from South Africa that demonstrated no association with TTAT [93]. On HIV duration variable, the findings demonstrated that increase of every 5 and 10 years of HIV survivorship explained a 24% and 42% negative association to rapid ART-initiation.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations